Identifying the Components of Providing Health Information Services to Patients in Hospital Libraries in Health Disasters by Meta-Synthesis Method - Roya Balaghiinaloo; Alireza Noruzi; Mohammadreza Esmaeili Givi (Tehran University of Medical Sciences, 2023)
Background and Aim: It is not possible to provide health information services in health crises without a comprehensive understanding of these services and how to provide them due to the health crisis. Based on this, the aim of the current research was to obtain comprehensive information about the components of providing health information services in health crises. Materials and Methods: The current research was conducted with a qualitative approach and a meta-combined method, using the seven-step method of Sandelowski and Barroso. The statistical population consisted of articles and theses published in persian and international databases between 1991 to 2022 AD and 1370 to 1400 solar. Out of a total of 8363 resources identified based on the critical skills assessment program, 40 resources were approved. Extracted information was coded and coding reliability was measured and confirmed using Kappa coefficient.  Results: From the results of the research, 74 codes were extracted in 21 concepts and 6 categories in the field of providing health information services to patients. which categories and codes include health information needs assessment (disease, health, health information sources, patients); accessibility and dissemination of health information (health information, access ways); Awareness and notification of health information (information, tools); Education (patients, managers and staff of hospital libraries, methods); Planning (health crisis, resources, budget, infrastructure, patients, librarians and Medical Information Specialists) and obstacles and limitations (expert force, budget, facilities and infrastructure and resources) were categorized. Conclusion: Dealing with the issue and components of providing health information services to patients in health Disasters in hospital libraries can cause policymakers in this field to know more about the dimensions, concepts, and consequences of providing these services in order to provide access to health information for everyone, especially patients. According to the identified components, efforts can be made to prepare the necessary infrastructure in order to plan to strengthen the strengths and eliminate the existing weaknesses and make appropriate policies in order to play the role of health counseling and launch the health information service department in hospital libraries.